Implementing a closed loop clinical decision support system for sustainable preoperative care - José Luis Gracia Martínez; Bernadette Pfang; Miguel Ángel Morales Coca; Cristina Caramés Sánchez; Marta del Olmo Rodríguez; Marco Antonio Villegas García; Jorge Short Apellaniz; Javier Arcos Campillo; Juan Antonio Álvaro de la Parra; Florencia Manzano Lorefice; Luis Enrique Muñoz Alameda (npj Digital Medicine)
Abstract Unnecessary preoperative testing poses a risk to patient safety, causes surgical delays, and increases healthcare costs. We describe the effects of implementing a fully EHR-integrated closed-loop clinical decision support system (CDSS) for placing automatic preprocedural test orders at two teaching hospitals in Madrid, Spain. Interrupted time series analysis was performed to evaluate changes in rates of preoperative testing after CDSS implementation, which took place from September 2019 to December 2019. We included 228,671 surgical procedures during a 69-month period from January 1st, 2018, to October 1st, 2023, of which 78,388 were from the preintervention period and 150,283 from the postimplementation period. We observed a significant reduction (p < 0.001) of 83% (−83.4% to −83.1%) for chest X-ray orders, 54% (−54.7% to −54.2%) for ECG orders, 50% for blood type testing (−50.5% to −50.1%), and 29% (−29.5% to −29.0%) for preoperative blood test order sets, leading to overall cost-savings of €1,013,666. No increase in postoperative adverse events or same-day cancellations was observed. Our results demonstrate that an EHR-embedded closed-loop CDSS can reduce avoidable preoperative testing without increasing surgical cancelations, postoperative adverse events, or early re-interventions, thus improving the quality of care and healthcare expenditure.